(untitled) (Research, Society and Development, 2022)
Lippia dulcis Trevir belongs to the Verbenaceae family and is popularly known as sweet grass. The objective of this work was to evaluate the flowering, fruiting and factors involved in the rooting of cuttings. Phenological evaluations were recorded monthly in the morning in 24 individuals (January 2016 to December 2018). Propagation by cuttings was carried out in two periods (cold and hot), with two substrates (commercial and sand) and three types of cuttings (apical, median and basal). Evaluation of the rooting of the cuttings was carried out during the period of 30 days with an interval of five days each after the transplanting of the cuttings (5, 10, 15, 20, 25 and 30 days). For the phenological evaluation, the longest flowering and fruiting period occurred from July to November, coinciding with the lowest average values ​​of rainfall. Plants showed higher number of shoots, branch length and purple leaves in full sun environment. In the rooting of cuttings, 100% of root induction was observed in both seasons, in the type of cutting and substrate. There was no significant difference for the biometric parameters in the different substrates. All cuttings showed roots and shoots from the 15th day after transplanting. The collection of plant material for medicinal use should be carried out in the months with the lowest number of flowering and fruiting. L. dulcis has a fast root development and an efficient rooting percentage, regardless of the type of cutting or substrate.